Reconciling irrigation demands for agricultural expansion with environmental sustainability - a preliminary assessment for the Ica Valley, Peru - Salmoral, Gloria; Carbó, Araceli Viñarta; Zegarra, Eduardo; Knox, Jerry W.; Rey, Dolores (Elsevier, 2020)
Irrigation expansion driven by a growing global food demand is threatening the sustainability of scarce water resources. An exemplar is the Ica Valley in Peru which has experienced significant agricultural transformation over the last three decades with uncontrolled abstractions leading to over-exploitation of the Ica-Villacuri aquifer. This paper critically assesses the impacts of agricultural expansion on the long-term sustainability of groundwater resources in the Ica Valley. We apply a combination of spatial analysis and irrigation modelling by farming type (large and small-scale), followed by a multi-criteria assessment on irrigation water use. Historical trends in cropped area were analysed using Landsat satellite imagery to identify agricultural expansion and the changing composition between large and small-scale farms. The blue water footprint (WFblue) for croplands was calculated distinguishing between surface and groundwater abstractions for eight disaggregated geographical zones within the Ica Valley. The economic benefits of water consumption were assessed using the water productivity indicator, and the environmental sustainability of water resources spatially evaluated using a monthly blue water sustainability index and adapted version of the groundwater debt. The analyses showed that the groundwater footprint accounts for 87% of the total WFblue (483 Mm3) with 286 Mm3 groundwater consumed under unsustainable conditions (exceeding groundwater recharge). The highest water productivity (2.4-5.4 sol/ton) occurs in zones with intensive groundwater abstractions and where most large-farms are located, but it is also where the sustainability issue is most acute. Modelling showed that based on existing climate conditions and cropping patterns, irrigated agriculture is locally unsustainable throughout the valley, with the exception of small-scale farming in the peri-urban and middle valley areas. Around 10% of total aquifer recharge results from small-scale irrigated farming, whereas recharge from large scale farming is negligible. The greatest impacts occur in zones dominated by large-scale farms, where a period of 3.7 to 5.9 years is estimated to be needed to replenish water resources consumed by agricultural production. There is thus an urgent need to manage water resources more effectively and promote more sustainable use of water to protect both traditional and agro-export agricultural practices as well as allocations for urban water supply and the environment
Keywords: water productivity; water footprint; groundwater; agro-export; Abstraction